Patterns of Sexual Behaviour and Reported Symptoms of STI/RTIs among Young People in Croatia – Implications for Interventions’ Planning - Božičević, Ivana (Array, 2006)
This paper describes some of the results of the first national-level survey on sexual behaviour and the distribution of risks to sexually transmitted infections (STIs), including human immunodeficiency virus infection (HIV), among youth in Croatia, and the nature and the extent of their vulnerability to these adverse health outcomes. The study was a cross- -sectional, probability-based household survey conducted in 2005, and included 1093 respondents aged 18– 24. This paper aims to describe the findings related to the knowledge of HIV transmission, key behavioural outcomes relevant for potential transmission of HIV and STIs, and correlates of genital discharge in young men and young women. More than 80% of young people know that the correct use of condoms protects against HIV and that HIV can be transmitted by someone who looks healthy. Fifty-nine percent of young men and 52.4% of young women reported using condoms during the first sexual intercourse, and 59.3% of men and 46.1% of women used condoms during the last sexual intercourse with a casual partner. This points to the gap between knowledge of condom use and the actual use of condoms as a high proportion of risky sexual contact remain unprotected. Having sexual intercourse frequently or regularly while consuming alcohol was reported by 19.2% of men and 7.6% of women. Much lower proportion are using drugs frequently or regularly during sexual intercourse (3.7% of men and 2.1% of women). Among those sexually experienced, 11.8% of men and 44.1% of women reported ever having a genital discharge. Higher presence of genital discharge in women is suggestive of reproductive tract infections that are not necessarily sexually transmitted. In the multivariate analysis, the lack of knowledge of whether chlamydial infections is an STI and having more than five partners in life were correlates of genital discharge in men, while in women the correlates included having more than five partners in life and not using condoms during the first sexual intercourse. Higher burden of STI-related symptoms was found among men who have men as sexual partners, those who paid for sex, and those with concurrent partnerships. These findings point out to the immediate need to strengthen sexual health education among young people and to the necessity for further development of other broad-based interventions to prevent adverse sexual health outcomes among both men and women, as well as those targeted towards more vulnerable subgroups.